ECRG4 Represses Cell Proliferation and Invasiveness via NFIC/OGN/NF-κB Signaling Pathway in Bladder Cancer - Liang, Xin; Gao, Jiangang; Wang, Quan; Hou, Sichuan; Wu, Changli (Frontiers in Genetics, 2020)
Bladder cancer (BCa) is a malignant tumour in the urinary system with high cancer-related mortality globally. However, the molecular mechanisms of numerous genes dysregulated in BCa are still unclear. Herein, we showed that Esophageal cancer-related gene-4 (ECRG4), which is downregulated in the BCa tissues and cell lines, has a positive association with Osteoglycin (OGN). Further functional experimental studies suggested that both the ECRG4 and the OGN inhibited cell proliferation, migration, and invasion in the BCa cells. Moreover, the ECRG4 acted as a tumour repressor and promoted the expression of the OGN via the upregulation of nuclear factor 1 C-type (NFIC), which could bind to the OGN promoter region and regulate its transcription. Bioinformatics analysis showed that the NFIC was downregulated in the BCa tissues and had a positive correlation with the ECRG4 or OGN. The ECRG4 could positively regulate the protein level of NFIC in the BCa cells. Also, we first demonstrated that ECRG4 inhibited the NF-κB signalling pathway via the upregulation of the OGN in the BCa cells. Overall, these findings provide the evidence that the ECRG4 and OGN both functioned as tumour repressors, and overexpression of the ECRG4 inhibited the NF-κB signalling pathway via promoting the NFIC/OGN signalling in the BCa cells. Our results revealed the molecular regulatory mechanisms of the ECRG4-mediated repression of the NFIC/OGN/NF-κB signalling pathway in BCa and provided potential biomarkers or therapeutic targets for BCa.